2001
DOI: 10.1210/jcem.86.3.7291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine on Cardiac Function and Structure in Subclinical Hypothyroidism: A Double Blind, Placebo-Controlled Study

Abstract: Subclinical hypothyroidism (sHT) affects 5-15% of the general population; however, the need of lifelong L-T(4) therapy is still controversial. As myocardium is a main target of thyroid hormone action, we investigated whether sHT induces cardiovascular alterations. Twenty sHT patients were randomly assigned to receive placebo or L-T(4) therapy and were followed for 1 yr. Twenty sex- and age-matched normal subjects served as controls. Doppler echocardiography and videodensitometric analysis were performed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(118 citation statements)
references
References 33 publications
6
107
3
2
Order By: Relevance
“…Rawat et al [17] also reported significant increase in LVPW in hypothyroid subjects. Bello et al [18] and Monzani et al [19] did not find similar incidence.…”
Section: Discussionmentioning
confidence: 84%
“…Rawat et al [17] also reported significant increase in LVPW in hypothyroid subjects. Bello et al [18] and Monzani et al [19] did not find similar incidence.…”
Section: Discussionmentioning
confidence: 84%
“…16,17 However, this suggestion was not confirmed by other studies. 13,15 Second, previous studies have clearly shown that patients with SHT have left ventricular diastolic dysfunction at rest that is reversible with thyroxine therapy 18,19 and systolic dysfunction on effort, which may result in poor physical exercise capacity. In the present study, we revealed that left ventricular diastolic function was impaired in patients with SHT as compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…SH has been consistently associated with mild diastolic dysfunction at rest and on effort, but the studies are limited by their small size, design and selection bias (148)(149)(150)(151)(152)(153)(154) (B,B,B,B,C,C,C,). In a moderate-sized community-based sample, no association was observed between higher serum TSH concentrations and echocardiographic measurements (155) (A).…”
Section: Is There An Association Between Heart Failure and Subclinicamentioning
confidence: 99%